2013
DOI: 10.3389/fncel.2013.00162
|View full text |Cite
|
Sign up to set email alerts
|

Wnts in action: from synapse formation to synaptic maintenance

Abstract: A proper balance between synapse assembly and disassembly is crucial for the formation of functional neuronal circuits and synaptic plasticity in the adult brain. During development, synaptogenesis generates a vast excess of synapses, which are subsequently eliminated. Importantly, aberrant synaptic disassembly during development underpins many neurological disorders. Wnt secreted proteins are robust synaptogenic factors that regulate synapse assembly and function in the developing and mature brain. Recent stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 111 publications
(215 reference statements)
1
78
0
1
Order By: Relevance
“…Numerous synaptogenic molecules, such as FGFs, Wnts, neurotrophins, Eph/ephrins, neurexins/neuroligins and leucine-rich repeat transmembrane proteins (LRRTMs), have been identified (Dai and Peng, 1995;Umemori et al, 2004;Terauchi et al, 2010;de Wit et al, 2011;Dickins and Salinas, 2013;Park and Poo, 2013;Siddiqui and Craig, 2011;Xu and Henkemeyer, 2012), but the underlying mechanisms through which they organize presynaptic differentiation are largely unknown. In this study, we demonstrated, using both in vivo and in vitro evidence, that differential use of FGFRs by FGF22 and FGF7 contributes to their presynaptic effects on excitatory and inhibitory synapses in the CA3 of the hippocampus, where the receptors are localized presynaptically in DGCs and interneurons, and that FGFR2b utilizes FRS2 and PI3K signaling to promote synaptic vesicle accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous synaptogenic molecules, such as FGFs, Wnts, neurotrophins, Eph/ephrins, neurexins/neuroligins and leucine-rich repeat transmembrane proteins (LRRTMs), have been identified (Dai and Peng, 1995;Umemori et al, 2004;Terauchi et al, 2010;de Wit et al, 2011;Dickins and Salinas, 2013;Park and Poo, 2013;Siddiqui and Craig, 2011;Xu and Henkemeyer, 2012), but the underlying mechanisms through which they organize presynaptic differentiation are largely unknown. In this study, we demonstrated, using both in vivo and in vitro evidence, that differential use of FGFRs by FGF22 and FGF7 contributes to their presynaptic effects on excitatory and inhibitory synapses in the CA3 of the hippocampus, where the receptors are localized presynaptically in DGCs and interneurons, and that FGFR2b utilizes FRS2 and PI3K signaling to promote synaptic vesicle accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for the involvement of Wnt signaling in learning and memory processes has been reported, because it modulates synaptic function, neuronal plasticity (Dickins and Salinas, 2013;Rosso and Inestrosa, 2013), as well as adult hippocampal neurogenesis (Varela-Nallar and Inestrosa, 2013). With regard to these facts, there are considerable amounts of data that relate defects in Wnt signaling with the pathogenesis of a number of neurodegenerative and psychiatric diseases, such as AD, Parkinson's disease, schizophrenia, bipolar disorder, and autism (Berwick and Harvey, 2014;Inestrosa et al, 2012;Okerlund and Cheyette, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…Wnt ligands and components of Wnt signaling pathways are expressed during cortical development, and Wnt signaling has a well-characterized role in embryonic neurogenesis (Chenn, 2008;Rakic et al, 2009). Moreover, Wnt signaling has been implicated in dendritic development and synapse formation of cortical neurons in culture (Dickins and Salinas, 2013). Evidence indicates that Wnt proteins guide cell migration and that multiple Wnt ligands and receptors directly regulate cell polarity and motility in a variety of vertebrate and invertebrate systems (Lyuksyutova et al, 2003;Witze et al, 2008;Mentink et al, 2014).…”
Section: Introductionmentioning
confidence: 98%